Where does the salt marsh start? Field-based evidence for the lack of a transitional area between a gradually sloping intertidal flat and salt marsh. (30th September 2020) - van Regteren, M.; Amptmeijer, D.; de Groot, A.V.; Baptist, M.J.; Elschot, K.
Abstract: Salt marshes are vegetated ecosystems between land and sea, hosting unique plant and animal communities, contributing to crucial habitats for birds and providing numerous other ecosystem services. They form a sustainable nature-based coastal protection, and its protective value increases with the width of the system. Salt marshes and their adjoining tidal flats are often studied separately. At present, there is a lack of studies that describe the features of these two systems in unison and in relation to each other. This study descriptively assesses an array of abiotic and biotic variables that potentially affect successful vegetation establishment. Unfavourable soil conditions may limit establishment as well as bioturbation of infauna. This is related to the marsh expansion potential and could aid in salt marsh restoration and marsh growth stimulation projects. In a naturally developing salt marsh, we sampled the elevation gradient from the tidal flat to the low marsh for benthic species composition, plant seed availability and abiotic variables. The abundance of benthos was highest landwards of the transition zone, in the pioneer zone. Distinct meiobenthic groups occurred in the different zones along the tidal flat to low marsh gradient, but macrobenthos was largely absent from the muddy soil. In the sparsely vegetated transition zone, the abundance of salt-marsh seeds was low, similar to the tidal flat. It suggests that, even though a seed source was in proximity, seed availability in spring was insufficient to achieve lateral marsh expansion. Clustering and nMDS analyses showed that an identifiable transition zone was lacking. The transition zone resembled the bare tidal flat in terms of its abiotic and biotic conditions. This was mainly driven by significant changes in soil oxygenation and seed availability. Graphical abstract: Image 1 Highlights: Plant, benthic and environmental characteristics determined on a tidal flat-salt marsh gradient. The transitional zone showed a shift to low soil oxygenation and near absence of seeds. The transition zone clustered with the elevated tidal flat. Benthic groups inhabited specific zones, macrobenthos were largely absent. Seed availability forms a threshold for lateral salt marsh expansion.